Screen time as discriminator for overweight, obesity and abdominal obesity in adolescents. - Pitanga, Francisco J. G. (2017)
Many researches have concluded that the time spent in front of TV, computer and other screen-type devices is an important risk factor for overweight and obesity. The aim of this study was to identify the discriminatory power and to propose screen time cutoff points for overweight, obesity and abdominal obesity in adolescents. This household survey had cross-sectional design with sample of 613 adolescents aged 15-18 years living in a city in northeastern Brazil. The predictive power and cutoffs points of screen time for the outcomes of interest were identified by receiver operating characteristic curves (ROC). The study adopted 95% confidence interval (CI). Screen time during one day on the weekend was a good discriminator for the presence of overweight only among girls, area under the curve ROC = 0.59 (0.51 to 0.65). There were no areas under the ROC curve with statistical significance to discriminate obesity and abdominal obesity. Remain sitting for accumulated four hours per day during the weekend discriminates presence of overweight among girls (sensitivity = 60.9%, specificity = 52%). The long time spent in front of TV, computer and other screen-type devices on the weekend discriminate overweight in girls.